(untitled) (African Journal of Biomedical Research, 2020)
Trauma is increasing amongst the children and is an important cause of pain. Less analgesia, if any at all, is given to children for pain. There is the need for accurate diagnosis of trauma pain, determination of its severity in children and use of the most effective treatment regimen. The study was a prospective observational study carried out at the Accidents and Emergency Department of the University College Hospital, Ibadan. A total sampling of all paediatric patients presenting with trauma pain over a 11-month period was done. An interviewer administered questionnaire was used to obtain information about patients’ demographics, pain experiences and interventions at different time intervals. Thirteen patients participated in the research of which most (69.2%) were males Trauma was more common amongst toddlers and school age children. The most common cause of trauma pain was Motor Vehicular Accidents (46.2%). Most patients (46%) had mild pain as their worst previous pain experience; however, about 62% of the patients experienced severe pain at the time of presentation to the hospital. Non-Steroidal Anti-inflammatory Drugs (NSAIDs) were the most commonly used analgesics. Only about 15% of the participants had an opioid analgesic alone or with an NSAID. Pain from trauma as experienced by children in this environment is usually moderate to severe but suffers oligoanaesthesia. A trauma pain treatment protocol should be developed to adequately address the needs of this patient population